(untitled) (SCIÉNDO INGENIUM, 2021)
In the search for agricultural irrigation systems that increase efficiency in the use of water, it was necessary to evaluate the uniformity and profitability of the irrigation system by exudation in the production of habanero pepper (Capsicum chinense Jacq.). A randomized complete block analysis of variance was performed, with two treatments (exudation and dripping) with four repetitions. Irrigation by exudation showed greater application efficiency with a sheet of usable moisture (LHA) of 0.395 cm per day, while the drip system showed a LHA of 0.470 cm. Irrigation by exudation in the same way presented a higher coefficient of flow uniformity with 93% while by dripping it showed 89%, when evaluating the coefficient of pressure uniformity, this was higher in irrigation by exudation with 98% while that by drip was 89%. In the economic aspect, the irrigation by exudation generated a profitability of 77.91% and by drip 68.68% with a higher benefit/cost ratio of irrigation by exudation (3.53) than drip irrigation (2.19). From the results it is concluded that exudation irrigation is a viable alternative for its use in the cultivation of habanero pepper.